In situ SERS monitoring of intracellular H2O2 in single living cells based on label-free bifunctional Fe3O4@Ag nanoparticles. Issue 9 (8th March 2022) - Wang, Yue; Cheng, Cheng; Ma, Ruofei; Xu, Zhangrun; Ozaki, Yukihiro
Abstract : Intracellular H2 O2  in single living cells was visualized by SERS technology using label-free bifunctional Fe3 O4 @Ag nanoparticles with ultra-sensitivity. Abstract : Visualization of signaling molecules in single living cells is crucial for understanding cellular metabolism and physiology, which can provide valuable insights into early diagnoses and treatments of diseases. Highly sensitive in situ monitoring of intracellular analytes released from single living cells by virtue of label-free nanosensors is urgently needed, which can avoid interferences from molecular labeling. Here, we proposed an ultrasensitive strategy for in situ imaging of intracellular H2 O2 in single living cancer cells by surface-enhanced Raman scattering (SERS) spectroscopy with the utilization of label-free Fe3 O4 @Ag core–satellite nanoparticles (NPs). The Fe3 O4 @Ag NPs can efficiently and selectively catalyze the oxidation of the peroxidase substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of H2 O2 . Additionally, they exhibit excellent SERS activity that allows for in situ monitoring of intracellular H2 O2 in living cells through establishing the correlation between the H2 O2 level and the SERS intensity of the catalytic oxidation product of TMB. The H2 O2 concentration is revealed through the SERS intensity of oxidized TMB with a good linear response in a wide range from 1 fM to 1 mM. Moreover, the intracellular H2 O2 level in live cancer cells and imaging of the distribution of H2 O2 inside single cells can be achieved by using such a label-free nanosensor based strategy. Our work demonstrates that the label-free Fe3 O4 @Ag NP-based SERS imaging and quantification strategy is a promising and powerful approach to assess intracellular H2 O2 in living cells and allows us to monitor single-cell signaling molecules with nanoscale resolution.